2021
DOI: 10.2196/25927
|View full text |Cite
|
Sign up to set email alerts
|

Usability and Acceptability of a Mobile App for the Self-Management of Alcohol Misuse Among Veterans (Step Away): Pilot Cohort Study

Abstract: Background Alcohol misuse is common among Operation Enduring Freedom and Operation Iraqi Freedom veterans, yet barriers limit treatment participation. Mobile apps hold promise as means to deliver alcohol interventions to veterans who prefer to remain anonymous, have little time for conventional treatments, or live too far away to attend treatment in person. Objective This pilot study evaluated the usability and acceptability of Step Away, a mobile app d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…The Step Away app was originally developed in 2013 and has undergone 4 major revisions based on user input and recommendations. A finding that has emerged frequently from research on Step Away is that the app’s ability to provide self-monitoring and tailored feedback to the user is a key driver of utilization [ 43 , 59 , 60 ], which has resulted in the feedback feature being prominent and well-developed. This was the first version of the bot, and, like many first versions, it had some unforeseen limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Step Away app was originally developed in 2013 and has undergone 4 major revisions based on user input and recommendations. A finding that has emerged frequently from research on Step Away is that the app’s ability to provide self-monitoring and tailored feedback to the user is a key driver of utilization [ 43 , 59 , 60 ], which has resulted in the feedback feature being prominent and well-developed. This was the first version of the bot, and, like many first versions, it had some unforeseen limitations.…”
Section: Discussionmentioning
confidence: 99%
“…We also had limited time to undertake this study and our 12-week follow-up period may have been insufficient for differences between interventions to emerge. Previous research with Step Away showed that participants continued to reduce their alcohol intake at 6 months [ 43 ] and that 45% of participants were still actively engaged at the 6-month follow-up. A 12-month follow-up would provide a more detailed picture of how users remain engaged with the interventions over time and how this engagement is related to improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an interesting study, Malte et al [10 ▪ ] examined the feasibility and acceptability of the ‘ Step Away’ app among 55 war veterans with excessive alcohol use (82% met DSM-5 criteria for AUD). Step Away includes self-monitoring, normative feedback, goal-setting, craving self-management, and social support.…”
Section: Alcohol Use Mhealth Appsmentioning
confidence: 99%
“…In most of their studies evaluating usability measurements at the prototype stage, research conducted in research [14] conducted usability testing on mobile applications for the health sector with 55 veteran respondents who had various characteristics from age, gender, skin colour, education, marital status, income, and the degree of propensity to alcoholism. Measurements were carried out for six months with a SUS value of 69.3 (SD 19.7) for the 1st month and 71.9 (SD 15.8) for the third month.…”
Section: Introductionmentioning
confidence: 99%